COMPREHENSIVE MANAGEMENT OF ORAL MUCOSAL DISORDERS IN PATIENTS WITH EPILEPSY: PATHOGENESIS, THERAPEUTIC STRATEGIES, AND CLINICAL OUTCOMES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Oral mucosal disorders are common yet often underestimated complications in patients with epilepsy. Chronic neurological dysfunction, long-term antiepileptic drug therapy, and neuroimmune dysregulation significantly affect the structural and functional integrity of the oral mucosa. These factors contribute to persistent inflammatory changes, increased susceptibility to infections, delayed tissue regeneration, and frequent disease recurrence. Standard dental treatment approaches often fail to achieve sustained remission due to the multifactorial nature of the pathology. The present article analyzes the pathogenetic mechanisms underlying oral mucosal disorders in patients with epilepsy and evaluates comprehensive management strategies integrating dental, neurological, and immunological perspectives. Clinical outcomes demonstrate that a multidisciplinary, pathogenetically oriented approach improves mucosal healing, reduces recurrence rates, and enhances patients’ quality of life.